Comprehensive Plasma N-Glycoproteome Profiling Based on EThcD-sceHCD-MS/MS - Mao, Yonghong; Su, Tao; Lin, Tianhai; Yang, Hao; Zhao, Yang; Zhang, Yong; Dai, Xinhua (Frontiers in Chemistry, 2022)
Glycoproteins are involved in a variety of biological processes. More than one-third of the plasma protein biomarkers of tumors approved by the FDA are glycoproteins, which could improve the diagnostic specificity and/or sensitivity. Therefore, it is of great significance to perform the systematic characterization of plasma N-glycoproteome. In previous studies, an integrated method based on combinatorial peptide ligands library (CPLL) and stepped collision energy/higher-energy collisional dissociation (sceHCD) was developed by us for comprehensive plasma N‑glycoproteome proﬁling. Recently, we presented a new fragmentation method, EThcD-sceHCD, which outperformed sceHCD in the accuracy of identification. Herein, we integrated CPLL into EThcD-sceHCD, and compared the performance of different mass spectrometry dissociation methods (EThcD-sceHCD, EThcD and sceHCD) in the intact N-glycopeptides analysis of prostate cancer plasma. The results illustrated that EThcD-sceHCD was better than EThcd and sceHCD in the numbers of identified intact N-glycopeptides (two folds). A combination of sceHCD and EThcD-sceHCD methods can cover almost all glycoproteins (96.4%) and intact N-glycopeptides (93.6%), indicating the good complementarity between the two. Our study has a great potential for the medium- and low-abundance plasma glycoprotein biomarker discovery.